2008
DOI: 10.1159/000124295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adenoidectomy and/or Tonsillectomy on Cardiac Functions in Children with Obstructive Sleep Apnea

Abstract: Background/Aims: We aimed to determine the effects of adenoidectomy and/or tonsillectomy (AT) on cardiac functions in children with adenoid and/or tonsillary hypertrophy and obstructive sleep apnea syndrome (OSAS) by using echocardiography with tissue Doppler imaging facility (TDI). Methods: Twenty-nine children with adenoid and/or tonsillary hypertrophy and OSAS and 26 children with primary snoring entered the study. Cardiac functions were assessed by echocardiography with TDI in both groups. Tests were repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 69 publications
2
53
0
Order By: Relevance
“…1 Several pathophysiologic mechanisms related to cardiovascular morbidity have also been identified in children with obstructive sleep apnea. Elevated blood pressure, 2 changes in cardiac structure and function, [3][4][5] increased fasting insulin and lipid levels, 6,7 chronic inflammation 8 and endothelial dysfunction 9 most likely predispose children with obstructive sleep apnea to future cardiovascular disease. All the above secondary effects of sleep apnea are probably the result of increased work of breathing, more negative than usual intrathoracic pressure, arousals from sleep and gas exchange abnormalities which are the immediate consequences of intermittent upper airway obstruction during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several pathophysiologic mechanisms related to cardiovascular morbidity have also been identified in children with obstructive sleep apnea. Elevated blood pressure, 2 changes in cardiac structure and function, [3][4][5] increased fasting insulin and lipid levels, 6,7 chronic inflammation 8 and endothelial dysfunction 9 most likely predispose children with obstructive sleep apnea to future cardiovascular disease. All the above secondary effects of sleep apnea are probably the result of increased work of breathing, more negative than usual intrathoracic pressure, arousals from sleep and gas exchange abnormalities which are the immediate consequences of intermittent upper airway obstruction during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia may result in respiratory acidosis which in turn may lead to pulmonary artery vasoconstriction and increased RV dysfunction. Pulmonary vascular resistance was clearly increased to maintain cardiac output and resulted in a dialated RV, increased pulmonary pressure and the development of cor pulmonae [2,5]. Symptoms of PH may not be obvious until severe cardiac decompensation [10].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between ATH and other diseases such as cardiovascular and pulmonary disorders was reported in previous studies [1][2][3][4]. It is well known that ATH is one of the most common causes of upper respiratory tract obstruction, obstructive sleep apnea (OSA) and hypoxia in children [2]. Severe upper respiratory tract obstruction may have an effect on chronic alveolar hypoventilation, which consequently may lead to right ventricle (RV) dysfunction induced by hypoxemic pulmonary vasoconstriction.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Mustafa et al .found that elevated PAP is present in 50 % of children undergoing tonsiloadenectomy [7]. Mehmet et al found a decrease in estimated pulmonary artery systolic pressure from 31±4.2 to 13.1 ± 2.3 after tonsillectomy and/ or adenoidectomy in adult [8].…”
Section: Tv : Tricuspid Valvementioning
confidence: 99%